DEVELOPMENT OF SCIENTIFIC PERFORMANCE ASSESSMENT INSTRUMENT IN THE PRACTICUM OF ZnO LEVEL ANALYSIS IN LOOSE POWDER - Ega Hidayani; Ida Farida; Risa Rahmawati Sunarya (UIN Sunan Gunung Djati Bandung, 2021)
One of the assessment instruments that can be used to assess the achievement of competence and process skills in practicum activities is performance assessment instrument. The instrument for assessing scientific performance in the practicum of ZnO level analysis in loose powder is needed. This study aimed to describe the appearance of the scientific performance assessment instrument in the form of practicum worksheets and student performance assessment sheets, and to analyze the results of the validation test of the two instruments. This research used the Design Based Research (DBR) method with the stages of analysis and product design development, starting from the analysis of relevant journals, making worksheets and performance assessment sheets, to validation tests for lecturers who are experts in chemistry and learning media. The worksheets consist of discourse, questions before and after conducting the experiment, analyzing the experimental data, concluding the experimental data, and making a report on the results of the experiment. The performance assessment sheets consist of performance assessment aspects, criteria, assessment rubric, and student identity. Based on the data from the validation test results to expert lecturers, valid worksheets and performance assessment were obtained with rcount values of 0.838 and 0.846 respectively.